Root Cause Analysis of Fatal Occupational Accidents in the South Pars Special Economic Energy Zone Using the Tripod-Beta Method(First Half of 2023) (Development Engineering Conferences Center Articles Database, 2025)
The aim of the present study was to identify the causes of occupational accidents among workers in the South Pars Special Economic Energy Zone during the first half of 2023. This was a descriptive-analytical study that employed the Tripod-Beta method to analyze fatal occupational accidents during this period. The study identified surface causes, preconditions, and latent causes, and developed incident trees for each case. The results of the analysis of fatal occupational accidents in the onshore construction phase of the gas refinery revealed six main risk factors contributing to these incidents: Responsibility/Organizational Influences (57.8%), Training (22.2%), Equipment, Machinery, and Tools (6.7%), Maintenance Management (6.7%), Operational Procedures (4.4%), and Error-Enhancing Conditions (2.2%).It was found that by addressing the two main factors—responsibility/organizational structure and training—more than 80% of fatal occupational accidents could potentially be prevented. Therefore, implementing effective worker supervision systems, employing workers with adequate knowledge and skills, and improving training indicators can enhance risk awareness, improve safety, and reduce the occurrence of accidents